Respuesta :

Abira
first option is right.

Answer:

First option.

Step-by-step explanation:

For a quadratic equation of the form:

a*x^2 + b*x + c = 0

we have that the solutions for x are:

[tex]x = \frac{-b +- \sqrt{b^2 - 4ac} }{2a}[/tex]

where we have two solutions, one for each sign of the square root.

then if our equation is:

5x^2 + 3x - 4 = 0

we have that 5 = a, 3 = b and -4 = c, then our equation is:

[tex]x = \frac{-3 +- \sqrt{3^2 - 4*5*(-4)} }{2*5}[/tex]

then the correct option is the first one.